Weighted $\ell_p$-Minimization for Sparse Signal Recovery under Arbitrary Support Prior (Analysis in Theory and Applications, 2022)
Weighted $\ell_p$ ($0
Keywords: Adaptive recovery; compressed sensing; weighted $\ell_p$ minimization; sparse representation; restricted isometry property.